The History of Transformation of Russian State System in Turkestan Exemplified by the Activities of the General-Governor’s Office - Bakhtiyar Ergashevich Ergashev (Researchparks Publishing, 2022)
The second half of the 19th and the beginning of the 20th century are largely characterized by radical changes in political and social-economical situation in Turkestan. The historical analysis of the above mentioned period requires multiple approaches while doing research into characteristics of that time. The main cause at the time was the Russian conquest and establishment of laws of the Russian Empire in the territories settled by numerous nationalities with their already formed life styles and economies.